Two new species of the genus Amiantofusus (Gastropoda: Fasciolariidae) from seamounts in the tropical western Pacific, with remarks on the taxonomy of A. candoris and A. sebalis - Zhang, Shuqian; Fraussen, Koen; Zhang, Suping (Frontiers in Marine Science, 2022)
During two scientific expeditions to seamounts near the Mariana Trench in the tropical western Pacific, two undescribed gastropod species belonging to the genus Amiantofusus Fraussen, Kantor & Hadorn, 2007 were collected from the upper bathyal zone. In the present study, we describe and illustrate them as new species. Amiantofusus granulus sp. nov. was collected from Magellan and Caroline Seamounts at depths of 1357–1473 m, and Amiantofusus tchangsii sp. nov. was discovered from Caroline Seamounts at depths 1893–2291 m. The new species are distinguished from each other and congeners by shell morphology. Phylogenetic analyses based on the cytochrome oxidase c subunit I (COI) gene using Bayesian inference indicate that Amiantofusus granulus sp. nov. is a sister group to other congeners, and Amiantofusus tchangsii sp. nov. shows a close relationship with Amiantofusus sp. JQ950210 from the Philippines. The results provide additional support for assignment of the new species to genus Amiantofusus, and separation of them from congeners. In addition, our molecular analysis reveals that Amiantofusus candoris Fraussen, Kantor & Hadorn, 2007 and Amiantofusus sebalis Fraussen, Kantor & Hadorn, 2007 have almost identical COI sequences. Their taxonomic relationship is briefly discussed and concludes that A. candoris should be regarded as a junior synonym of A. sebalis.